Inflammatory Bowel Disease in Young Adult - Dian Daniella; Janto Simkoputera; Candra Wiguna (The Indonesian Society for Digestive Endoscopy, 2019)
Inflammatory bowel disease is a chronic inflammatory disease that consist of Crohn’s disease and ulcerative colitis. A dramatic increase in the prevalence if inflammatory bowel disease (IBD) within developing countries including in Asia makes IBD a substantial global medical burden and modern refractory disease, and it is imperative that Asian healthcare systems especially physician are aware of this and familiar with the clinical manifestation and management. The aim of this case report is to present a case of IBD in young adult in Indonesia. Patient came with complaint of chronic diarrhea and had seen multiple doctor without improvement. Inflammatory bowel disease should always be considered in patient with chronic diarrhea with or without extraintestinal manifestation especially after poor response of usual antidiarrheal medication. Diagnosing of IBD is based on clinical manifestation, physical examination, laboratory result and endoscopy. Until now, ileocolonoscopy and biopsy is the most accurate diagnostic modality for IBD and can be used to differentiate between ulcerative colitis and Crohn’s disease. Treatment of IBD are drugs such as mesalazine until surgery based on the severity or complication of disease.